Nail disorders : a comprehensive approach - Singal, Archana; Neema, Shekhar; Kumar, Piyush, 1982- (New York, NY : CRC Press/Taylor & Francis Group, 2019)
Nail disorders are a specialized group of disorders which are often neglected during post graduate teaching. This book aims to provide a comprehensive review covering the diagnostic and therapeutic aspects of nail disorders. It discusses the basics of nail unit, common conditions like infections, tumors and genetic diseases, diagnostic armamentarium involved in nail diseases like KOH mount, onychoscopy, imaging and surgical management of nail diseases which includes anesthesia of nail unit, nail biopsy and advanced nail procedures including video demonstration of such procedures. This book elaborates on nails in systemic diseases and briefly covers nail cosmetics and nail photography. Key Features Comprehensively reviews nail disorders Includes diagnosis, therapeutic and surgical aspect Discusses Onychoscopy Reviews the importance of nail photography Includes video demonstration of nail surgery
OCLC-licensed vendor bibliographic record.
Keywords: Nails (Anatomy) -- Diseases; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / Dermatology; MEDICAL / Infectious Diseases; MEDICAL / Family & General Practice